House Cricket, Acheta domesticus (Linnaeus) - T.J. Walker (EDIS)
This document provides a comprehensive profile of the house cricket, Acheta domesticus. It covers the cricket's distribution, life cycle, identification, habitat, and song. The article highlights the cricket's role as bait for fish and food for pets, its inability to survive in the wild in peninsular Florida, and its rearing methods. It also discusses management strategies for house crickets that escape into homes. The document is part of the Featured Creatures collection, aimed at both laypersons with some biological knowledge and academic audiences. Published: January 1999.